Bipolar pole piece of all-solid-state battery and all-solid-state battery thereof

By using the method of clamping the solid electrolyte layer on both sides of the electrode layers and adding a conductive layer between the electrode layer and the insulating layer in an all-solid state battery, the problem of intimate interface bonding during winding is solved, the internal resistance is reduced, and the Battery conductivity and performance.

CN119275226APending Publication Date: 2025-01-07SODIUM TECHNOLOGY CO
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411385883.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

Smart Images

  • Figure CN119275226A_ABST
    Figure CN119275226A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, in particular to an all-solid-state battery bipolar pole piece and an all-solid-state battery thereof. The pole piece comprises a first current collector insulating layer, a first current collector conducting layer, a first electrode layer, a solid electrolyte layer, a second electrode layer, a second current collector conducting layer and a second current collector insulating layer which are sequentially adhered and connected from bottom to top, and tabs are led out from the side edges of the first current collector conducting layer and the second current collector conducting layer. Aiming at the problems of loose interface bonding and large conduction internal resistance during winding of a solid-state battery in the prior art, good contact between solid interfaces is realized by selecting a structure that a solid electrolyte layer is clamped by electrode layers on two sides in the embodiment; and the conductive layer is added between the electrode layer and the insulating layer to form a conduction channel of the upper layer, so that equipotential of each part of the electrode layer is realized, the conductivity between electrolyte interfaces in the solid-state battery is further improved, and the internal resistance is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a bipolar pole piece of an all-solid-state battery and an all-solid-state battery thereof. Background Art

[0002] Solid-state batteries are a type of battery technology. Unlike the lithium-ion batteries and lithium-ion polymer batteries commonly used today, solid-state batteries are batteries that use solid electrodes and solid electrolytes. Since the scientific community believes that lithium-ion batteries have reached their limits, solid-state batteries have been seen in recent years as batteries that can inherit the status of lithium-ion batteries. Solid-state lithium battery technology uses solid electrolytes as conductive materials to replace the electrolytes of previous lithium batteries. Due to the density and structure of solid electrolytes, more charged ions can be gathered at one end, conducting a larger current, thereby increasing the battery capacity. Therefore, for the same amount of electricity, the solid-state battery will become smaller. Not only that, since there is no electrolyte in solid-state batteries, sealing will become easier, which not only saves costs but also effectively reduces weight.

[0003] In the prior art, there are corresponding all-solid-state battery solutions. For example, Chinese patent CN202110689670.9 discloses a method for preparing a wound bipolar battery and a wound bipolar battery, the preparation method comprising the following steps: coating the positive electrode active slurry and the negative electrode active slurry on the first and second sides of the bipolar current collector respectively, drying after coating, and then rolling and slicing to obtain a bipolar sheet; coating either the first side or the second side with a solid electrolyte, and coating the edge area of ​​the bipolar sheet with an insulating glue; stacking and bonding n bipolar sheets in a manner that the bonding surfaces of adjacent bipolar sheets have opposite polarities, and then coating the solid electrolyte on the surface of the bonded bipolar sheet to obtain an n-layer bipolar sheet, where n ≥ 2; winding the n-layer bipolar sheet into a battery cell, welding the pole ears at the tail of the n-layer bipolar sheet, drying and encapsulating, and obtaining a wound bipolar battery. By using bipolar current collectors, the battery generates high voltage, and winding the stacked bipolar sheets increases the energy density by more than 10% compared to the series-connected batteries of the same system.

[0004] However, during the actual implementation process, the inventors found that in this type of technical solution, since a solid electrolyte is applied to one side of the bipolar pole piece to form a solid electrolyte layer, and then the solid electrolyte is brought into contact with the positive and negative electrodes by winding, the problem of loose interface bonding between the solids may occur during the winding process, thereby increasing the internal resistance of the battery. Summary of the invention

[0005] In view of the above problems existing in the prior art, an all-solid-state bipolar pole piece is provided; on the other hand, a method for manufacturing the all-solid-state bipolar pole piece is also provided; on the other hand, a battery using the all-solid-state bipolar pole piece is also provided.

[0006] The specific technical solutions are as follows:

[0007] An all-solid bipolar pole piece, comprising a first current collector insulating layer, a first current collector conductive layer, a first electrode layer, a solid electrolyte layer, a second electrode layer, a second current collector conductive layer and a second current collector insulating layer, which are sequentially bonded and connected from bottom to top;

[0008] Tabs are extended from the sides of the first current collector conductive layer and the second current collector conductive layer.

[0009] On the other hand, both the first current collector insulating layer and the second current collector insulating layer are current collector insulating layer structures;

[0010] The current collector insulating layer structure is formed by at least one material selected from the group consisting of PET, PP, PE, PI, and nano-ceramic materials.

[0011] On the other hand, the first current collector conductive layer and the second current collector conductive layer are formed of metal microporous foil or metal etched foil;

[0012] The metal microporous foil or the metal corrosion foil is made of copper, aluminum or steel.

[0013] On the other hand, the first electrode layer or the second electrode layer is a positive electrode layer;

[0014] The positive electrode active material of the positive electrode layer includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, layered sodium oxide, and sodium iron pyrophosphate.

[0015] On the other hand, the first electrode layer or the second electrode layer is a cathode layer;

[0016] The negative electrode active material of the negative electrode layer includes at least one of graphite, nano silicon, hard carbon and soft carbon.

[0017] On the other hand, one of the first electrode layer and the second electrode layer is a positive electrode layer, and the other one of the first electrode layer and the second electrode layer is a negative electrode layer;

[0018] The ratio of the surface density of the negative electrode layer to the surface density of the positive electrode layer is between 1:4 and 1:1;

[0019] The area of ​​the negative electrode layer is greater than that of the positive electrode layer.

[0020] On the other hand, the solid electrolyte layer includes a polymer solid electrolyte and at least one of an oxide solid electrolyte and a sulfide electrolyte;

[0021] The surface of the oxide solid electrolyte and / or the sulfide solid electrolyte in the solid electrolyte layer is uniformly coated by the polymer solid electrolyte, and the coating thickness is 1 to 50 nm.

[0022] On the other hand, the polymer solid electrolyte includes at least one of PEO, PMMA, PVDF, PVC, PAN, PC, PDMS, PEEK, and PCTFE;

[0023] The oxide solid electrolyte includes Li7La3Zr2O 12 , Li 1+x Al x Ti 2-x (PO4)3, LiTaO3, LiNbO3, Na3Zr2Si2PO 12 At least one of 0 <x<2;

[0024] The sulfide solid electrolyte includes Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Na3PS4, Na3SbS4, Na2S-P2S5, Na 11 Sn2PS 12 At least one of .

[0025] In another aspect, the solid electrolyte layer further includes an electrolyte salt.

[0026] A method for manufacturing an all-solid-state bipolar pole piece, used for preparing the above-mentioned all-solid-state bipolar pole piece;

[0027] The production method comprises:

[0028] Step S1: sequentially pasting the first current collector insulating layer, the first current collector conductive layer and the first electrode layer to form a first composite layer, and sequentially pasting the second current collector insulating layer, the second current collector conductive layer and the second electrode layer to form a second composite layer;

[0029] Step S2: pressing the first composite layer, the solid electrolyte layer and the second composite layer to form the all-solid-state bipolar pole piece.

[0030] A battery, comprising the above-mentioned all-solid-state bipolar pole piece,

[0031] On the other hand, the battery includes one or more of the all-solid-state bipolar pole pieces.

[0032] On the other hand, the all-solid-state bipolar pole pieces are wound to form the battery core of the battery, or the all-solid-state bipolar pole pieces are stacked to form the battery core of the battery.

[0033] The above technical solution has the following advantages or beneficial effects:

[0034] In view of the problem that solid-state batteries in the prior art are prone to loose interface bonding and large conduction internal resistance during winding, this embodiment selects a structure in which the solid electrolyte layer is clamped by electrode layers on both sides to achieve good contact between the solid interfaces, and a conductive layer is added between the electrode layer and the insulating layer to form a conduction channel for the upper layer, thereby achieving equal potential at various locations on the electrode layer, further improving the conductivity between the electrolyte interfaces in the solid-state battery and reducing the internal resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The embodiments of the present invention will be described more fully with reference to the attached drawings, which are provided for illustration and description only and are not intended to limit the scope of the present invention.

[0036] Figure 1 It is an overall schematic diagram of an embodiment of the present invention;

[0037] Figure 2 Schematic diagram of the method in an embodiment of the present invention. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0040] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.

[0041] The present invention comprises:

[0042] An all-solid-state bipolar pole piece, such as Figure 1 As shown, including:

[0043] A first current collector insulating layer 1;

[0044] A first current collector conductive layer 2, the first current collector conductive layer 2 is adhered on the first current collector insulating layer 1;

[0045] A first electrode layer 3, the first electrode layer 3 is attached above the first current collector conductive layer 2;

[0046] A solid electrolyte layer 4, the solid electrolyte layer 4 is adhered on the first electrode layer 3;

[0047] A second electrode layer 5, the second electrode layer 5 is pasted on the solid electrolyte layer 4;

[0048] A second current collector conductive layer 6, which is adhered on the second electrode layer 5;

[0049] A second current collector insulating layer 7, the second current collector insulating layer 7 is adhered on the second current collector conductive layer 6;

[0050] Tabs are extended from the sides of the first current collector conductive layer 2 and the second current collector conductive layer 6 .

[0051] Specifically, in view of the problem that solid-state batteries in the prior art are prone to loose interface bonding and large conduction internal resistance during winding, this embodiment selects a structure in which the solid electrolyte layer is clamped by electrode layers on both sides to achieve good contact between the solid interfaces, and forms a conduction channel for the upper layer by adding a conductive layer between the electrode layer and the insulating layer, thereby achieving equal potential at various locations on the electrode layer, further improving the conductivity between the electrolyte interfaces in the solid-state battery and reducing the internal resistance.

[0052] Specifically, the all-solid-state bipolar pole piece in this solution adopts a technical solution in which a solid electrolyte layer 4 is sandwiched between the positive and negative electrodes to form a bipolar pole piece.

[0053] Taking the embodiment in which the first electrode layer 3 is a positive electrode layer and the second electrode layer 5 is a negative electrode layer as an example, in this embodiment, the all-solid bipolar pole piece can be disassembled into a bottom positive electrode part, an upper positive electrode part and a solid electrolyte layer 4. The positive electrode part, the solid electrolyte layer 4 and the negative electrode part can be sequentially formed into a composite bipolar pole piece by processes such as pasting and pressing. Since each layer in the plane is joined, a relatively uniform solid interface contact can be achieved, thereby achieving good conductive characteristics.

[0054] On this basis, for the first electrode layer 3 and the second electrode layer 5, a first current collector conductive layer 2 is provided between the first electrode layer 3 and the first current collector insulating layer 1, and a second current collector conductive layer 6 is provided between the second electrode layer 5 and the second insulating layer 7, so as to form an additional conductive layer between the electrode and the insulating layer. The conductive layer can be used as an additional interlayer conduction channel during use to achieve equipotential at various locations on the electrode, so that the solid electrolyte layer 4 achieves relatively uniform ion conduction, further reducing the internal resistance of the battery.

[0055] At the same time, in order to facilitate processing, in this embodiment, after determining the above-mentioned structure, the first current collector insulating layer 1 and the second current collector insulating layer 7 are designed to wrap the front and back sides of the pole piece to form an insulating layer, and the pole ears are led out through the side, so that the all-solid-state bipolar pole piece can be directly used in the production of different types of batteries, such as winding or lamination, without considering insulation problems, thereby improving production efficiency.

[0056] In one embodiment, the first current collector insulating layer 1 and the second current collector insulating layer 7 are formed by using current collector insulating layers;

[0057] The current collector insulating layer includes at least one of PET, PP, PE, PI and nano-ceramic materials.

[0058] Specifically, to achieve better insulation effect, in this embodiment, the current collector insulating layer is determined to be at least one of PET, PP, PE, PI, and nano-ceramic materials, and the first current collector insulating layer 1 and the second current collector insulating layer 7 are prepared using the same or different insulating layer materials.

[0059] Furthermore, the thickness of the first current collector insulating layer 1 and the second current collector insulating layer 7 is between 1 and 10 um, and the thicknesses thereof may be the same or different.

[0060] In one embodiment, the first current collector conductive layer 2 and the second current collector conductive layer 6 are formed of metal microporous foil or metal corrosion foil;

[0061] The material of the metal microporous foil or metal corrosion foil is copper, aluminum or steel.

[0062] Specifically, in order to make the first electrode layer 3 and the second electrode layer 5 have a good conduction effect and form an equipotential, in this embodiment, a metal microporous foil or a metal corrosion foil is selected to form the first current collector conductive layer 2 and the second current collector conductive layer 6, and the rough surface is formed by preparing the microporous foil or the corrosion foil, which is convenient for combining the polymer insulating material and the electrode material on both sides, especially forming a good interface contact with the electrode material, and reducing the interface resistance during charge transfer. The thickness of the current collector conductive layer is 1 to 10 um, and the two sides can be the same or different.

[0063] In one embodiment, the first electrode layer 3 or the second electrode layer 5 is a positive electrode layer;

[0064] The positive electrode active material of the positive electrode layer includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, layered sodium oxide, and sodium iron pyrophosphate;

[0065] The first electrode layer 3 or the second electrode layer 5 is a negative electrode layer;

[0066] The negative electrode active material of the negative electrode layer includes at least one of graphite, nano silicon, hard carbon and soft carbon.

[0067] The thickness of the positive electrode layer is between 50 and 300 um, and the thickness of the negative electrode layer is between 0 and 250 um. According to the material selection, a negative electrode-free battery cell can be prepared.

[0068] In one embodiment, the first electrode layer 3 and the second electrode layer 5 include a positive electrode layer and a negative electrode layer;

[0069] The ratio of the surface density of the negative electrode layer to the surface density of the positive electrode layer is between 1:4 and 1:1;

[0070] The area of ​​the negative electrode layer is larger than that of the positive electrode layer.

[0071] Specifically, in order to achieve effective wrapping of the positive electrode layer by the negative electrode layer, in this embodiment, the ratio of the surface density of the negative electrode layer to the surface density of the positive electrode layer is controlled between 1:4 and 1:1, and the area of ​​the negative electrode layer is made larger than the area of ​​the positive electrode layer to achieve effective wrapping of the positive electrode layer.

[0072] In one embodiment, the solid electrolyte layer 4 includes a polymer solid electrolyte and at least one of an oxide solid electrolyte and a sulfide electrolyte;

[0073] The polymer solid electrolyte includes at least one of PEO, PMMA, PVDF, PVC, PAN, PC, PDMS, PEEK, and PCTFE;

[0074] Oxide solid electrolytes include Li7La3Zr2O 12 , Li 1+x Al x Ti 2-x (PO4)3, LiTaO3, LiNbO3, Na3Zr2Si2PO 12 At least one of 0 <x<2;

[0075] Sulfide solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Na3PS4, Na3SbS4, Na2S-P2S5, Na 11 Sn2PS 12 At least one of .

[0076] Specifically, in order to achieve a better ion conduction effect, in this embodiment, a polymer solid electrolyte is first prepared as a substrate, and then an oxide solid electrolyte and / or a sulfide solid electrolyte are added to the polymer solid electrolyte as a conductive filler, and the surface of the oxide solid electrolyte and / or the sulfide solid electrolyte is controlled to be uniformly coated by the polymer solid electrolyte, and the coating thickness is 1 to 50 nm, thereby achieving a more uniform and effective ion conduction process. At the same time, in some embodiments, an electrolyte salt can also be added, and the electrolyte salt is at least one of LiPF6, LiBF4, LiTFSI, LiFSI, NaPF6, NaBF4, NaTFSI, and NaFSI.

[0077] A method for preparing the above-mentioned all-solid-state bipolar pole piece, such as Figure 2 As shown, including:

[0078] Step S1: sequentially pasting the first current collector insulating layer, the first current collector conductive layer and the first electrode layer to form a first composite layer, and sequentially pasting the second current collector insulating layer, the second current collector conductive layer and the second electrode layer to form a second composite layer;

[0079] Step S2: Pressing the first composite layer, the solid electrolyte layer and the second composite layer to form an all-solid bipolar pole piece.

[0080] Based on the above arrangement, the above method can be used to prepare a fully solid bipolar pole piece, thereby solving the problem of loose interface bonding that may be caused by the winding process in the prior art.

[0081] Specifically, taking the above-mentioned manufacturing method as an example, the first composite layer and the second composite layer are first prepared separately, including pasting the first current collector insulating layer, the first current collector conductive layer and the first electrode layer in sequence; pasting the second current collector insulating layer, the second current collector conductive layer and the second electrode layer in sequence. Since both parts have an insulating layer as a substrate, they can be better combined and stored. Then, in the subsequent process, the first composite layer, the solid electrolyte layer and the second composite layer are pressed, preferably by a hot pressing composite process, so as to form a complete pole piece, and avoid the problem of poor interface bonding that may occur during the winding contact process, thereby reducing the internal resistance.

[0082] A battery, comprising the above-mentioned all-solid-state bipolar pole piece,

[0083] In one embodiment, the battery includes an all-solid-state bipolar pole sheet;

[0084] Alternatively, the battery includes a plurality of all-solid-state bipolar pole pieces;

[0085] The all-solid-state bipolar pole pieces are wound to form the battery core of the battery, or the all-solid-state bipolar pole pieces are stacked to form the battery core of the battery.

[0086] Specifically, after obtaining the above-mentioned all-solid-state bipolar pole pieces, the pole pieces can be combined using the following embodiments, including winding, lamination, series-parallel connection, etc., so as to prepare a battery roll core that meets the requirements.

[0087] Specifically, the following embodiments may be included:

[0088] 1. Winding batteries:

[0089] 1) Monopolar solid-state wound battery: Use one all-solid-state bipolar pole sheet to make a monopolar solid-state wound battery by winding.

[0090] In this embodiment, the battery roll core includes only one electrode sheet, which is formed by winding. Since the surface of the electrode sheet is an insulating layer and the electrode ear is led out from the side, the inner side of the electrode sheet can be either the positive electrode or the negative electrode, and the outer side is the opposite negative electrode or positive electrode, and no malfunction will occur due to contact.

[0091] 2) Multi-electrode series high voltage wound battery:

[0092] In this embodiment, the battery core includes a plurality of all-solid-state bipolar pole pieces, which are welded in series in the positive and negative directions to form a larger series-connected pole piece, and then the series-connected pole pieces are wound to form a high-voltage wound battery.

[0093] The battery includes multiple all-solid-state bipolar pole pieces, which are greater than two, and the total voltage is U=u*n, where u is the voltage of the all-solid-state bipolar pole piece and n is the number of all-solid-state bipolar pole pieces connected in series.

[0094] 3) Multi-electrode parallel high-capacity wound battery:

[0095] In this embodiment, a plurality of all-solid bipolar pole pieces are included, wherein the all-solid bipolar pole pieces are stacked in a specific number of layers, and then connected in parallel by welding to form a parallel pole piece, and then the parallel pole pieces are wound to form a battery core and loaded into the battery.

[0096] The capacity of the battery is C=c*n, where c is the capacity of the all-solid-state bipolar pole piece, and n is the number of all-solid-state bipolar pole pieces connected in parallel, which is generally 2-3.

[0097] 2. Laminated batteries:

[0098] 1) Multi-electrode series high voltage stacked battery:

[0099] In this embodiment, the battery core includes multiple all-solid-state bipolar pole pieces, which are welded in series in the positive and negative directions to form a larger series-connected pole piece, which is then folded, or the above process is repeated to obtain multiple series-connected pole pieces, which are then stacked and welded in parallel to form a stacked core and loaded into the battery.

[0100] 2) Multi-electrode parallel high-capacity stacked battery:

[0101] In this embodiment, a plurality of all-solid bipolar pole pieces are included, wherein the all-solid bipolar pole pieces are stacked in a specific number of layers, and then connected in parallel by welding to form a parallel pole piece, and then the parallel pole pieces are wound to form a battery core and loaded into the battery.

[0102] Since this solution adopts a structure in which the positive and negative electrodes directly contact the solid electrolyte layer and are wrapped with an insulating layer on both sides, it can achieve good battery life in various configurations, as follows:

[0103] Embodiment 1:

[0104] In this embodiment, the positive electrode layer material with the ternary material LiNi8Co1Mn1O2 as the active material is made into a dry film as the positive electrode layer by a dry method; the negative electrode layer material with graphite as the active material is made into a dry film as the negative electrode layer by a dry method; and the negative electrode layer material with Li7La3Zr2O 12 A dry membrane was made of the main electrolyte as the solid electrolyte layer, and aluminum foil was used to prepare the current collector conductive layer on the positive electrode side and the current collector conductive layer on the negative electrode side, and PET film was used as the insulating layer wrapping material.

[0105] In the preparation process, the PET film is used as the substrate on the positive electrode side, and the current collector conductive layer and the positive electrode layer are sequentially attached thereon, and a portion of the current collector conductive layer is cut to expose the positive electrode tab to form a positive electrode composite material;

[0106] On the negative electrode side, a PET film is used as a substrate, a current collector conductive layer and a negative electrode layer are sequentially attached thereto, and a portion of the current collector conductive layer is cut to expose the negative electrode tab, thereby forming a negative electrode composite material;

[0107] The positive electrode composite material, negative electrode composite material and solid electrolyte layer obtained above are hot pressed and composited into an all-solid-state bipolar pole piece; then a winding core is prepared by winding to form a 2Ah steel shell cylindrical all-solid-state battery. This assembly is the assembly method of a conventional all-solid-state battery and will not be repeated here.

[0108] Embodiment 2:

[0109] Different from the first embodiment, the present embodiment uses all-solid-state bipolar pole pieces to be wound into a square winding core to form a 2Ah aluminum-plastic film soft-package square all-solid-state battery, and the rest is the same as the first embodiment.

[0110] Embodiment three:

[0111] Different from the first embodiment, this embodiment uses all-solid-state bipolar pole pieces to be wound into a square winding core to form a 2Ah aluminum shell square all-solid-state battery, and the rest is the same as the first embodiment.

[0112] Embodiment 4:

[0113] Different from the first embodiment, the active material of the positive electrode sheet of this embodiment is NaNi3Fe3Mn3Cu1O2, and the solid electrolyte used is Na3Zr2Si2PO 12 The active material used in the corresponding negative electrode is hard carbon, and the solid electrolyte is also Na3Zr2Si2PO 12 , that is, the all-solid-state battery assembled in this embodiment is an all-solid-state sodium ion battery.

[0114] The rest is the same as in the first embodiment and will not be described again here.

[0115] Comparative Example 1:

[0116] Different from the first embodiment, the positive electrode sheet and the negative electrode sheet in this comparative example are independent electrode sheets, and aluminum corrosion foil and PET film are respectively pasted on one side;

[0117] The positive electrode sheet, the negative electrode sheet and the solid electrolyte layer are then combined and wound into a cylindrical core.

[0118] The rest is the same as in the first embodiment and will not be described again here.

[0119] Comparative Example 2:

[0120] Different from the second embodiment, in this comparative example, the positive electrode sheet and the negative electrode sheet are independent electrode sheets, and the positive electrode sheet, the negative electrode sheet and the solid electrolyte layer are composited and wound into a square winding core.

[0121] The rest is the same as the second embodiment and will not be described again here.

[0122] The all-solid-state batteries obtained in the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 2 were subjected to performance tests, including battery impedance, rate and cycle performance tests.

[0123] The impedance test method is:

[0124] The battery SOC is adjusted to 50% with a current of 0.5C, left for 2 hours, and the voltage U0 is recorded. The battery is then discharged at a constant current of 1.5C for 30 seconds, and the voltage U1 is recorded. The DCR is calculated as: (U0-U1) / I(1.5C).

[0125] The rate test method is:

[0126] Charge with 0.5C current to the upper cut-off voltage; leave for 30 min; discharge with 0.2C current to the lower cut-off voltage, record the capacity C0; leave for 30 min; charge with 0.5C current to the upper cut-off voltage; leave for 30 min; discharge with 1C current to the lower cut-off voltage, record the capacity C1; calculate the rate retention rate: (C1 / C0*100%).

[0127] The cycle performance test method is:

[0128] Charge with 0.5C current to the upper cut-off voltage; leave for 30 minutes; discharge with 0.5C current to the lower cut-off voltage; leave for 30 minutes; repeat the above steps for 200 cycles; record the capacity C1 of the first cycle, and record the capacity C200 of the 200th cycle; calculate the cycle capacity retention rate: (C200 / C1*100%).

[0129] The test results are shown in Table 1 below.

[0130]

[0131] Table 1 Test data of each group of embodiments and comparative examples

[0132] It can be seen from the above embodiments that the all-solid-state bipolar pole piece prepared in this solution can achieve good rate and capacity retention under any packaging and material ratio. The battery prepared by Examples 1 to 4 of the present invention has significantly better battery performance than that of Comparative Examples 1 and 2, with lower internal resistance, higher rate and better capacity retention.

[0133] In addition, since the positive and negative electrodes and the solid electrolyte in this scheme are directly hot-pressed and composited, it has a better contact interface than the winding contact process, thereby reducing the internal resistance of the battery, as follows:

[0134] Comparative Example 3:

[0135] In this embodiment, the materials of the positive electrode layer, the negative electrode layer and the solid electrolyte layer are prepared by the same process as in Example 1, and aluminum foil is used to prepare the current collector conductive layer on the positive electrode side and the current collector conductive layer on the negative electrode side, respectively, and PET film is used as the insulating layer wrapping material.

[0136] In the preparation process, the PET film is used as a substrate on the positive electrode side, and the current collector conductive layer and the positive electrode layer are sequentially attached thereon, and a portion of the current collector conductive layer is cut to expose the positive electrode tab to form a positive electrode composite material;

[0137] On the negative electrode side, a PET film is used as a substrate, a current collector conductive layer and a negative electrode layer are sequentially attached thereto, and a portion of the current collector conductive layer is cut to expose the negative electrode tab, thereby forming a negative electrode composite material;

[0138] Subsequently, the current collector insulating layer parts of the positive electrode composite material and the negative electrode composite material are pasted back to back, so that the positive electrode layer and the negative electrode layer are exposed on the two sides of the electrode sheet respectively.

[0139] A solid electrolyte layer is pasted on one side, such as the positive electrode layer or the negative electrode layer, and then the battery core is wound through a winding process. During the winding process, a certain pressure is applied to make the solid electrolyte layer combine with the negative electrode layer or the positive electrode layer on the opposite side, and then baked and solidified.

[0140] The embodiment 1 and the comparative example 3 were subjected to aging attenuation tests, and then their internal resistance, discharge rate and cycle performance were measured.

[0141] The testing process includes:

[0142] Charge with 0.5C current to the upper cut-off voltage; leave for 30 minutes; discharge with 0.5C current to the lower cut-off voltage; leave for 30 minutes; repeat the above steps for 200 cycles, and then conduct internal resistance, discharge rate and cycle performance tests.

[0143] in:

[0144] The impedance test method is:

[0145] The battery SOC is adjusted to 50% with a current of 0.5C, left for 2 hours, and the voltage U0 is recorded. The battery is then discharged at a constant current of 1.5C for 30 seconds, and the voltage U1 is recorded. The DCR is calculated as: (U0-U1) / I(1.5C).

[0146] The rate test method is:

[0147] Charge with 0.5C current to the upper cut-off voltage; leave for 30 min; discharge with 0.2C current to the lower cut-off voltage, record the capacity C0; leave for 30 min; charge with 0.5C current to the upper cut-off voltage; leave for 30 min; discharge with 1C current to the lower cut-off voltage, record the capacity C1; calculate the rate retention rate: (C1 / C0*100%).

[0148] The cycle performance test method is:

[0149] Before starting the aging experiment, the initial capacity C1 was recorded. After the aging experiment, the battery was charged with a current of 0.5 C to the upper cut-off voltage as the 200th cycle capacity C200. The cycle capacity retention rate was calculated as: (C200 / C1*100%).

[0150] The test results are shown in Table 2:

[0151]

[0152] Table 2

[0153] It can be seen that after 200 cycles, the measured internal resistance of Example 1 using the above structure is significantly lower than that of Comparative Example 3, indicating that the battery roll core has better solid interface contact and better performance in rate and cycle retention.

[0154] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.

Claims

1. A fully solid bipolar pole piece, characterized in that: It includes a first current collector insulating layer, a first current collector conductive layer, a first electrode layer, a solid electrolyte layer, a second electrode layer, a second current collector conductive layer and a second current collector insulating layer which are sequentially bonded and connected from bottom to top; Tabs are extended from the sides of the first current collector conductive layer and the second current collector conductive layer.

2. The all-solid-state bipolar pole piece according to claim 1, characterized in that: The first current collector insulating layer and the second current collector insulating layer are both current collector insulating layer structures; The current collector insulating layer structure is formed by at least one material selected from the group consisting of PET, PP, PE, PI, and nano-ceramic materials.

3. The all-solid-state bipolar pole piece according to claim 1, characterized in that: The first current collector conductive layer and the second current collector conductive layer are formed by using metal microporous foil or metal corrosion foil; The metal microporous foil or the metal corrosion foil is made of copper, aluminum or steel.

4. The all-solid-state bipolar pole piece according to claim 1, characterized in that: The first electrode layer or the second electrode layer is a positive electrode layer; The positive electrode active material of the positive electrode layer includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, layered sodium oxide, and sodium iron pyrophosphate.

5. The all-solid-state bipolar pole piece according to claim 1, characterized in that: The first electrode layer or the second electrode layer is a negative electrode layer; The negative electrode active material of the negative electrode layer includes at least one of graphite, nano silicon, hard carbon and soft carbon.

6. The all-solid-state bipolar pole piece according to claim 1, characterized in that: One of the first electrode layer and the second electrode layer is a positive electrode layer, and the other of the first electrode layer and the second electrode layer is a negative electrode layer; The ratio of the surface density of the negative electrode layer to the surface density of the positive electrode layer is between 1:4 and 1:1; The area of ​​the negative electrode layer is greater than that of the positive electrode layer.

7. The all-solid-state bipolar pole piece according to claim 1, characterized in that: The solid electrolyte layer includes a polymer solid electrolyte and at least one of an oxide solid electrolyte and a sulfide electrolyte; The surface of the oxide solid electrolyte and / or the sulfide solid electrolyte in the solid electrolyte layer is uniformly coated by the polymer solid electrolyte, and the coating thickness is 1 to 50 nm; The polymer solid electrolyte includes at least one of PEO, PMMA, PVDF, PVC, PAN, PC, PDMS, PEEK, and PCTFE; The oxide solid electrolyte includes Li7La3Zr2O 12 , Li 1+x Al x Ti 2-x (PO4)3, LiTaO3, LiNbO3, Na3Zr2Si2PO 12 At least one of 0 <x<2; The sulfide solid electrolyte includes Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Na3PS4, Na3SbS4, Na2S-P2S5, Na 11 Sn2PS 12 At least one of .

8. A method for manufacturing an all-solid-state bipolar pole piece, characterized in that: Used to prepare the all-solid-state bipolar pole piece as claimed in any one of claims 1 to 7; The production method comprises: Step S1: sequentially pasting the first current collector insulating layer, the first current collector conductive layer and the first electrode layer to form a first composite layer, and sequentially pasting the second current collector insulating layer, the second current collector conductive layer and the second electrode layer to form a second composite layer; Step S2: Pressing the first composite layer, the solid electrolyte layer and the second composite layer to form the all-solid-state bipolar pole piece.

9. A battery, characterized in that: Comprising a fully solid-state bipolar pole piece as described in any one of claims 1-9.

10. The battery according to claim 9, characterized in that The battery comprises one or more all-solid-state bipolar pole pieces; The all-solid-state bipolar pole pieces are wound to form the battery core of the battery, or the all-solid-state bipolar pole pieces are stacked to form the battery core of the battery.

Citation Information

Patent Citations

  • Preparation method of wound bipolar battery and wound bipolar battery

    CN113571754A